Taxonomic review of Ophiothrix Müller & Troschel, 1840 (Echinodermata: Ophiuroidea) from Brazil, with the description of four new species - Santana, Alisson; Manso, Cynthia L.c.; Almeida, Ana C.s.; Alves, Orane F.s. (Zootaxa, 2020)
Brittle stars are considered one of the main benthic groups at the Brazilian coast, where they occur in high abundance and diversity. Ophiothrix Müller & Troschel, 1840 is among the most common genera of ophiuroids, with hundreds of specimens deposited in Brazilian Zoological Collections. Here we reviewed the species of Ophiothrix of Brazil and elucidated the taxonomic status of the six species previously reported in Brazilian waters—Ophiothrix ailsae Tommasi, 1970, Ophiothrix angulata (Say, 1825), Ophiothrix brachyactis H. L. Clark, 1915, Ophiothrix rathbuni Ludwig, 1882, Ophiothrix suensoni Lütken, 1856 and Ophiothrix trindadensis Tommasi, 1970. Three of these were not found among the 1.134 specimens analyzed in this study—O. ailsae, O. angulata and O. brachyactis. Most specimens previously attributed to these three taxa are here assigned to Ophiothrix brasiliensis n. sp. due having disc covered by short spines with 2–6 thorns at the apex and triangular radial shields covered only by short bifid and trifid spines. Three other new species are also described. Ophiothrix spiniformis n. sp. has a disc covered by long spines with denticules along their complete length and an apex with spinelets and radial shields covered by short bifid and trifid spines. Ophiothrix tommasii n. sp. is characterized by the interradial regions of the disc and radial shields being covered by spines with 2–7 thorns at the tip, and by the presence of small spines on the first dorsal arm plate. Ophiothrix troscheli n. sp. has a disc covered by long conical spines and naked, triangular radial shields. An identification key for the Ophiothrix species of Brazil is provided.